Investigation of the time resolution of 3D silicon sensors. (1st December 2022) - Diehl, L.; Ferrer, O.; Hauser, M.; Jakobs, K.; King, M.; Kramberger, G.; Moffat, N.; Parzefall, U.; Pellegrini, G.; Sperlich, D.
Abstract: Collider experiments as the upcoming Phase II-LHC or the future circular collider (FCC) will increase the demands on tracking detectors. In the FCC hadron collider, sensors will not only face fluences up to 1 × 10 17 neq /cm 2, but also high pile-up scenarios. Therefore, sensors will be required not only to have a good spatial resolution and a very high radiation hardness, but also an excellent time resolution of the order of 5 ps. Currently, Low Gain Avalanche Diodes (LGADs) are one of the main candidates when it comes to timing, achieving a resolution well below 30 ps. However, their radiation hardness is not sufficient for future colliders. 3D sensors are an interesting alternative due to their superior radiation hardness. In 3D sensors, which already have been thoroughly investigated for tracking purposes, the drift distances are short, the depletion voltage is very low and the electric field can be very high, thus the signals are fast and short. In this study, the time resolution of different 3D sensors was investigated with signals generated by MIP-like electrons, as well as by measurements using a laser with an infrared wavelength. It is shown that 3D pixel sensors can achieve time resolutions competitive with those of LGADs. Additionally, Transient Current Technique (TCT) timing measurements have been conducted. These allow to study the position dependence of the time resolution, which is interesting for 3D sensors due to their complex electric field structure. The measurements prove the direct correlation between the time resolution and the electric field configuration. Furthermore, the performance of the sensors is demonstrated before and after irradiation with reactor neutrons.